Consider $f: R _{+} \rightarrow[-5, \infty)$ given by $f(x)=9 x^{2}+6 x-5 .$ Show that $f$ is invertible with $f^{-1}(y)=\left(\frac{(\sqrt{y+6})-1}{3}\right)$
$f : R _+\rightarrow[-5, \infty)$ is given as $f ( x )=9 x ^{2}+6 x -5$
Let $y$ be an arbitrary element of $[-5, \infty)$
Let $y=9 x^{2}+6 x-5$
$\Rightarrow y=(3 x+1)^{2}-1-5=(3 x+1)^{2}-6$
$\Rightarrow y+6=(3 x+1)^{2}$
$\Rightarrow 3 x+1=\sqrt{Y+6}$ $[$ as $y \geq-5 \Rightarrow y+6>0]$
$\Rightarrow x =\left(\frac{(\sqrt{ y +6})-1}{3}\right)$
$\therefore f$ is onto, thereby range $f =[-5, \infty)$
Let us define $g:[-5, \infty) \rightarrow R_+$ as $g(y)=\left(\frac{(\sqrt{y+6})-1}{3}\right)$
Now, $(gof)(x)=g(f(x))=g\left(9 x^{2}+6 x-5\right)$ $=g\left((3 x+1)^{2}-6\right)$
$=\sqrt{(3 x+1)^{2}-6+6}-1$
$=\frac{3 x+1-1}{3}=\frac{3 x}{3}=X$
and
$(\text { fog })(y)=f(g(y))=\left(\frac{\sqrt{Y+6}-1}{3}\right)$ $=\left[3\left(\frac{\sqrt{Y+6}-1}{3}\right)+1^{2}\right]-6$
$=(\sqrt{Y+6})^{2}-6=+6-6=y$
$\therefore gof=x=I_{R}$ and $fog$ $=y=I_{R a n g e} f$
Hence, $f$ is invertible and the inverse of $f$ is given by
$f^{-1}(y)=g(y)=\left(\frac{\sqrt{Y+6}-1}{3}\right)$
Let $S=\{a, b, c\}$ and $T=\{1,2,3\} .$ Find $F^{-1}$ of the following functions $F$ from $S$ to $T$. if it exists. $F =\{( a , 3),\,( b , 2),\,( c , 1)\}$
Let $f:\left[ {4,\infty } \right) \to \left[ {1,\infty } \right)$ be a function defined by $f\left( x \right) = {5^{x\left( {x - 4} \right)}}$ then $f^{-1}(x)$ is
Consider $f: R _{+} \rightarrow[4, \infty)$ given by $f(x)=x^{2}+4 .$ Show that $f$ is invertible with the inverse $f^{-1}$ of $f$ given by $f^{-1}(y)=\sqrt{y-4},$ where $R ^{+}$ is the set of all non-negative real numbers.
Let $f: W \rightarrow W$ be defined as $f(n)=n-1,$ if is odd and $f(n)=n+1,$ if $n$ is even. Show that $f$ is invertible. Find the inverse of $f$. Here, $W$ is the set of all whole numbers.
If $f: R \rightarrow R$ be given by $f(x)=\left(3-x^{3}\right)^{\frac{1}{3}},$ then $fof(x)$ is ..........